2016
DOI: 10.1364/ol.41.003415
|View full text |Cite
|
Sign up to set email alerts
|

Versatile digital micromirror device-based method for the recording of multilevel optical diffractive elements in photosensitive chalcogenide layers (AMTIR-1)

Abstract: A new alternative and versatile method for the production of diffractive optical elements (DOEs) with up to four phase levels in AMTIR-1 (Ge33As12Se55) layers is demonstrated. The developed method proposes the use of the photosensitive properties of the layers and a specific in situ optical monitoring coupled with a reverse engineering algorithm to control the trigger points of the writing of the different diffractive patterns. Examples of various volume DOEs are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The traditional fabrication methods of CGHs or DOEs rely on photolithographic processes that require several steps and can be time-consuming. In recent works, it has been shown that basic diffractive optical elements could be recorded in chalcogenide layers based on photo-induced refractive index change [2,3]. However, due to limited refractive index change, thick layers, up to 15-25 µm, were required to generate the desired phase change.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional fabrication methods of CGHs or DOEs rely on photolithographic processes that require several steps and can be time-consuming. In recent works, it has been shown that basic diffractive optical elements could be recorded in chalcogenide layers based on photo-induced refractive index change [2,3]. However, due to limited refractive index change, thick layers, up to 15-25 µm, were required to generate the desired phase change.…”
Section: Introductionmentioning
confidence: 99%